Salivary immune proteins monitoring can help detection of binge and chronic alcohol drinkers: Preliminary findings. (1st February 2018) - Waszkiewicz, Napoleon; Galińska-Skok, Beata; Zalewska, Anna; Szajda, Sławomir Dariusz; Zwierz, Krzysztof; Więdłocha, Magdalena; Szulc, Agata
Highlights: Binge drinking disturbs salivary innate immunity (lisozyme). Chronic drinking disturbs adaptive and innate immunity (IgA, lisozyme, lactoferrin). IgA and oral peroxidase may help to differentiate binge and chronic drinking. Abstract: Background: We compared effects of binge and chronic alcohol drinking on oral health and salivary immunity proteins. Methods: The study involved males: 13 healthy social-drinking (C), 10 alcohol-dependent after chronic alcohol-intoxication (A), and 8 binge-drinkers after a single binge-drinking session (B). We compared periodontal/dental state and salivary immune proteins (lactoferrin –Lf, lysozyme –Lz, oral peroxidase –OPO, immunoglobulin A –IgA) in all groups. Results: Group A had worse dental and periodontal states than group C and B. Group B had a lower OPO activity and Lz concentration, and a higher IgA concentration in comparison to group C. Group A had a higher OPO activity than group C. Group B had a lower Lz and a higher LF and IgA outputs than C. Group A had a lower IgA output and a strong tendency of Lf and Lz outputs to be lower than in group C. Positive correlations were found between alcohol amounts and OPO and Lf output in group A, with no such correlations in group B. Only IgA concentration in group B and OPO activity in group A have potential to be markers that help to differentiate binge from chronic alcohol drinking, and OPO activity had better accuracy than IgA. Conclusion: Binge alcohol consumption resulted in specific disturbances in salivary innate immunity (Lz), whereas chronic drinking led to disturbances in both adaptive and innate immunity (IgA, Lz and Lf). There is potential applicability of raised salivary IgA concentration and especially OPO activity in binge and chronic drinking detection and differential-diagnosis.